Circulating tumor DNA as a biomarker and liquid biopsy in head and neck squamous cell carcinoma. Issue 7 (15th March 2018) - Payne, Karl; Spruce, Rachel; Beggs, Andrew; Sharma, Neil; Kong, Anthony; Martin, Timothy; Parmar, Satyesh; Praveen, Prav; Nankivell, Paul; Mehanna, Hisham
Abstract: The use of circulating biochemical molecular markers in head and neck cancer holds the promise of improved diagnostics, treatment planning, and posttreatment surveillance. In this review, we provide an introduction for the head and neck surgeon of the basic science, current evidence, and future applications of circulating tumor DNA (ctDNA) as a biomarker and liquid biopsy to detect tumor genetic heterogeneity in patients with head and neck squamous cell carcinoma (HNSCC).